Torsion-induced failure of a reinforced thermoplastic pipe used in a gas lift system. (February 2023) - Kong, Lushi; Li, Houbu; Wei, Bin; Zhu, Wenfeng; Li, Xianming; Yan, Zifeng; Chen, Qingguo; Liang, Xiaofei; Xia, Mingming
Highlights: This paper first reports a torsion-induced failure of a reinforced thermoplastic pipe (RTP) serviced in a gas lift system. Performance of liner pipe and reinforcement fibers deteriorated due to torsion, resulting in failure. The conveying medium caused the liner pipe and the reinforced fibers to swell. The reinforced fibers were contaminated with the medium because of joint leakage induced by damage to the sealing ring. Abstract: After servicing for 4.5 years, a reinforced thermoplastic pipe utilized in a gas lift system experienced a burst failure. FTIR, visual inspection, TGA, tensile test, VST, pressure test, DSC, and torsion test were performed to investigate the root cause for the failure. The findings demonstrate that the failed pipe had suffered serious torsion. The torsion led to the significant performance deterioration of reinforced fibers and liner pipe. The liner pipe has multiple torsion morphologies. Tensile test results show that torsion led to the deterioration of the mechanical properties of the liner pipe, especially the modulus (14.7%). There was a 60–80% drop in both elongation at the break and tensile strength of the fibers. Results from the torsion-pressure test illustrate that torsion would lead to a decline in the pipe's pressure capacity. The operating record indicates that this pipeline was a gas lift pipeline with long-term and high-pressure operations and weekly sweeping operations in winter. The pressure fluctuation was relatively frequent. The pipe failed when the instantaneous pressure exceeded the torsional pipe's capacity.